Mobile Banking Adoption Among SMEs: Driving Factors and Barriers in the Digital Transformation Era - David Simenyo; Ebuele Nobuse (Journal of Current Research In Multidisciplinary, 2026)
The digital transformation era has significantly reshaped the financial services landscape, prompting Small and Medium Enterprises (SMEs) to increasingly consider mobile banking as a viable tool for managing business transactions. This study examines the driving factors and barriers influencing mobile banking adoption among SMEs using a quantitative survey-based approach with 250 respondents. Drawing on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), the study analyzed five key constructs: perceived usefulness, perceived ease of use, security and privacy concerns, infrastructure readiness, and social influence. Data were analyzed using Structural Equation Modeling (SEM) via SmartPLS software. The findings reveal that perceived usefulness, perceived ease of use, infrastructure readiness, and social influence positively and significantly influence mobile banking adoption, while security and privacy concerns serve as the most critical barrier. These results highlight the necessity of coordinated efforts among financial institutions, technology developers, and policymakers to enhance platform usability, strengthen cybersecurity frameworks, and expand digital infrastructure to accelerate mobile banking adoption among SMEs.